Survey-based data on food security, nutrition and agricultural production shocks among rural farming households in northern Uganda - Mwungu, Chris Miyinzi; Shikuku, Kelvin Mashisia; Atibo, Christopher; Mwongera, Caroline (Elsevier, 2019)
Climate change, degradation of natural resources, conflict or civil war, diseases and poverty are among the key threats that impact agriculture, human nutrition, food security and food safety among rural households in developing countries. Sustainability of food systems and livelihoods will thus crucially depend on not only the ability to accommodate or recover from these threats but also to tap into opportunities for strengthening long-term capabilities. One approach to enhancing resilience to enhance food security and nutrition is building an evidence base to better understand the various types of smallholders, threats to agriculture production and the associated risks to food security and nutrition and household food preferences. Unfortunately, such data in many African countries is still unavailable or has not been shared publicly. In this paper, we describe data that were collected in Nwoya district, Northern Uganda in December 2017. These data can be used to assess the relationship between resilience of farm households to climatic risks and their food and nutrition security.